1998
DOI: 10.1080/15216549800202782
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the upstream region of Clostridium botulinum type B neurotoxin gene

Abstract: The upstream region of the gene coding for Clostridium botufinum type B (BoNT/B) neurotoxin was cloned and sequenced. There were two open reading frames, which were identified as a nontoxic-nonhemagglutinin component (ntnh/B) and a 22 kDa adjacent open reading frame (orf22/B). Deduced primary structure of ntnh/B showed that it was composed of 1,197 amino acid residues. Pairwise comparisons of the ntnh/B component with other botulinum toxin types showed high degree of homology to ntnh/A (82% identity). Northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Northern analyses of RNA isolated from these strains (Fig. 3) showed two type B-speci¢c transcripts with sizes (4 and 6 kb) corresponding approximately to those reported previously for the type A gene [16], and slightly smaller than those reported for the type B gene [17]. Several poorly resolved bands ( 9 1.9 kb) were also detected and attributed to degradation.…”
Section: Expression Analyses Of the Type B Neurotoxin Mrnasupporting
confidence: 70%
See 2 more Smart Citations
“…Northern analyses of RNA isolated from these strains (Fig. 3) showed two type B-speci¢c transcripts with sizes (4 and 6 kb) corresponding approximately to those reported previously for the type A gene [16], and slightly smaller than those reported for the type B gene [17]. Several poorly resolved bands ( 9 1.9 kb) were also detected and attributed to degradation.…”
Section: Expression Analyses Of the Type B Neurotoxin Mrnasupporting
confidence: 70%
“…To determine whether this might be the case, we compared the levels of type B toxin-speci¢c mRNA recovered from strains 588 and 593. Thus, di¡erences responsible for the phenotypic di¡erences in expression must be localized to a more distal region of the genome, possibly from a transcriptional readthrough from a second more distal promoter that directs expression of the NTNH gene located immediately upstream of the neurotoxin gene [17]. 3) showed two type B-speci¢c transcripts with sizes (4 and 6 kb) corresponding approximately to those reported previously for the type A gene [16], and slightly smaller than those reported for the type B gene [17].…”
Section: Expression Analyses Of the Type B Neurotoxin Mrna For Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…3, lane 2) were similar to those of 12S and 16S toxins, respectively, of other serotypes (2,4,6,12,13), and the N-terminal sequences were identical to those deduced from the nucleotide sequences of the serotype B toxin genes previously published (Fig. 3) (15,19,20,21). Thus, it was concluded that the molecular compositions of serotype B 12S and 16S toxins are similar to those of other serotypes.…”
supporting
confidence: 56%